Fiscal and monetary policies in complex evolving economies - Giovanni Dosi; Giorgio Fagiolo; Mauro Napoletano; Andrea Roventini; Tania Treibich (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
In this paper we explore the effects of alternative combinations of fiscal and monetary policies under different income distribution regimes. In particular, we aim at evaluating fiscal rules in economies subject to banking crises and deep recessions. We do so using an agent-based model populated by heterogeneous capital- and consumption-go od firms, heterogeneous banks, workers/consumers, a Central Bank and a Government. We show that the model is able to reproduce a wide array of macro and micro empirical regularities, including stylised facts concerning financial dynamics and banking crises. Simulation results suggest that the most appropriate policy mix to stabilise the economy requires unconstrained counter-cyclical fiscal policies, where automatic stabilisers are free to dampen business cycles fluctuations, and a monetary policy targeting also employment. Instead, "discipline-guided" fiscal rules such as the Stability and Growth Pact or the Fiscal Compact in the Eurozone always depress the economy, without improving public finances, even when escape clauses in case of recessions are considered. Consequently, austerity policies appear to be in general self-defeating. Furthermore, we show that the negative effects of austere fiscal rules are magnified by conservative monetary policies focused on inflation stabilisation only. Finally, the effects of monetary and fiscal policies become sharper as the level of income inequality increases.
Keywords: C63; E32; E6; E52; G01; G21; O4; 330; agent-based model; fiscal policy; monetary policy; banking crises; income inequality; austerity policies; disequilibrium dynamics